Gender and bargaining: Experimental evidence from rural Uganda - Ben d' Exelle; Christine Gutekunst; Arno Riedl (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We study gender differences in bilateral bargaining using an artefactual field experiment in rural Uganda, through variation in gender composition of bargaining pairs and in disclosure of identities. Disagreement is common independently of disclosure condition, but less frequent among female-only pairs. When paired with a man who is informed about their identity, women tend to demand less than men in the same situation. The influence of beliefs on demands is stronger for men than for women, and this difference is larger under anonymity than when identities are disclosed. These results identify important mechanisms that induce gender inequality in resource access.
Keywords: J16; O12; C93; 330; artefactual field experiment; bargaining; gender